Algebra of Bergman Operators with Automorphic Coefficients and Parabolic Group of Shifts - Mozel’, V. A.; Chernetskii, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
UDC 517.983We study the algebra of operators with the Bergman kernel extended by isometric weighted shift operators. The coefficients of the algebra are assumed to be automorphic with respect to a cyclic parabolic group of fractional-linear transformations of a unit disk and continuous on the Riemann surface of the group. By using an isometric transformation, we obtain a quasiautomorphic matrix operator on the Riemann surface with properties similar to the properties of the Bergman operator. This enables us to construct the algebra of symbols, devise an efficient criterion for the Fredholm property, and calculate the index of the operators of the algebra considered.